A Serious Case of Poisoning Caused by Oral Ingestion of Water-Soluble Fertilizer - Wei Ye; Shirong Lin; Chengquan Zheng; Chunshui Cao (Emergency Care and Medicine)
Current research is mostly focused on the impact of fertilizers on human health when they are ingested through food; the main form of this is chronic damage. Intoxication through oral ingestion of fertilizer is an extremely rare situation. We report a case of a 38-year-old man that attempted to commit suicide by ingesting only 20 mL of a water-soluble fertilizer. Acute kidney injury occurred early, which showed that the toxicity could not be ignored. It was necessary to seek medical attention as soon as possible. In addition, the patient experienced gastrointestinal dysfunction and a severe inflammatory response; inflammatory markers increased rapidly. Physicians implemented antimicrobial stewardship to reduce antimicrobial drug resistance and the risk of hospital infection, and the patient’s inflammatory response was well controlled. Although the damage was severe, the patient quickly recovered to normal after appropriate treatment. The prognosis is very good. This successful case provides guidance for clinical treatment.